2007
DOI: 10.1017/s0014479706004200
|View full text |Cite
|
Sign up to set email alerts
|

INFLUENCE OF CASSAVA (MANIHOT ESCULENTA) INTERCROP ON GROWTH AND FRUIT YIELDS OF PEPPER (CAPSICUM SPP.) IN SOUTH-WESTERN NIGERIA

Abstract: In tropical Africa, pepper (Capsicum spp.) is grown as a rainfed crop, and its production is limited by the long, hot growing season. Field experiments were conducted in Nigeria to evaluate the effects of cassava (Manihot esculenta) on the growth and yields of three pepper cultivars and gross returns in 2001-2003 was planted between rows of cassava cvs Idileru (PI), Odongbo (PO) and TMS 30572 (PT). In Experiment 2, pepper cvs Sombo, Tatase and Atarodo, were mixed with TMS 30572 (MS, MT or MA). The growth envir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…Factors such as whether peppers are the primary crop in the system (Kabura et al, 2008;Olasantan et al, 2007;Sharma and Bajaj, 1998), the timing of the intercrop planting (Duval, 2005;Guldan et al, 1997b), climatic conditions (Prabhakar and Shukla, 1990), pest pressure (Emeasor and Ezueh, 1997;Hooks and Johnson, 2001;Sharma and Bajaj, 1998), and local economics (Guldan et al, 1998;Kaur and Khurana, 2008;Ram and Kumar, 1998) all contribute to the potential success or failure of intercropping with peppers. Positive results are most likely to occur when plant-to-plant competition can be minimized, for example when peppers are used as intercrops in young orchards (Aiyelaagbe, 2001) or in hedgerow crops (Chen et al, 1989).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Factors such as whether peppers are the primary crop in the system (Kabura et al, 2008;Olasantan et al, 2007;Sharma and Bajaj, 1998), the timing of the intercrop planting (Duval, 2005;Guldan et al, 1997b), climatic conditions (Prabhakar and Shukla, 1990), pest pressure (Emeasor and Ezueh, 1997;Hooks and Johnson, 2001;Sharma and Bajaj, 1998), and local economics (Guldan et al, 1998;Kaur and Khurana, 2008;Ram and Kumar, 1998) all contribute to the potential success or failure of intercropping with peppers. Positive results are most likely to occur when plant-to-plant competition can be minimized, for example when peppers are used as intercrops in young orchards (Aiyelaagbe, 2001) or in hedgerow crops (Chen et al, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…Spurge family (Euphorbiaceae) Olasantan et al (2007) evaluated the effects of cassava (Manihot esculenta) on the growth and yields of pepper compared with sole cropping. Cassava tuber yield was unaffected by intercropping with pepper, and total gross returns were greater with intercropping than with growing either cassava or pepper in monoculture.…”
Section: Bromeliad Family (Bromeliaceae)mentioning
confidence: 99%
“…Pepper (Capsicum spp), member of the Solanaceae family with upright growth habit, are well adapted to sole-cropping and intercropping system. Several successful combination of pepper with other crops in intercropping has been reported [8,9,10,11]. The success or failure of intercropping pepper depends on whether pepper is the main crop or as secondary crop in the intercrop [12].…”
Section: Introductionmentioning
confidence: 99%
“…Conditions of the 2002 cropping season were more favourable for soyabean and sunflower production because they were wetter and cooler than in 2001. Although changes in microclimate due to intercropping were not investigated in this study, Olasantan (2007) and Olasantan et al (2007) revealed that substantial variations in soil moisture, light interception, and air, canopy and soil temperatures under intercropping were favourably modified to benefit the growth of component crops. However, lack of appreciable yield reduction of Record and Isaanka in the mixtures suggests that these varieties have some level of compatibility with soyabean, especially TGx 1440-1E and TGx 1448-2E, compared with var.…”
Section: Discussionmentioning
confidence: 89%